In vivo role of α-mannosidase IIx: ineffective spermatogenesis resulting from targeted disruption of the Man2a2 in the mouse - Fukuda, Michiko N; Akama, Tomoya O (BBA - General Subjects, 2002)
Alpha-mannosidase IIx (MX) is an enzyme closely related to the Golgi N-glycan processing enzyme α-mannosidase II (MII). The enzymatic activity of MX in vitro is minimal. Therefore, the in vivo role of MX in N-glycan processing is as yet unclear. The targeted disruption of the gene encoding MX in the mouse resulted in an obvious phenotype, i.e., MX-deficient males were found to be infertile. Testes from homozygous mutant male mice are smaller than those from wild-type or heterozygous littermates. Histology of the MX null mouse testis showed significant reduction of spermatogenic cells in the seminiferous tubules. Electron microscopy showed that prominent intercellular spaces surround MX-deficient spermatogenic cells, suggesting a failure of germ cell adhesion to Sertoli cells. Quantitative structural analyses of N-glycans from wild-type and MX-deficient mouse testis showed that wild-type testes contain GlcNAc-terminated complex type N-glycans, while they are significantly reduced in MX-deficient mutant testis. An in vitro assay for adhesion of spermatogenic cells to Sertoli cells was carried out. By testing the effect of each purified N-glycan oligosaccharide, it was demonstrated that a GlcNAc-terminated tri-antennary, fucosylated N-glycan has an activity on the adhesion between germ cells and Sertoli cells. Thus, the targeted disruption of the gene encoding MX uncovered a novel carbohydrate recognition system in a biologically important process, spermatogenesis.